Zero-Trust Security Concept and Its Implementation in Cloud-Edge Environment - Sreelatha R (Generate Digital Publishing, 2025)
Objective: This study aims to explore high-tech companies' understanding and perceptions of the Zero-Trust Security (ZTS) concept, identify the main challenges of its implementation in cloud–edge architectures, and analyze the security strategies used to effectively implement Zero-Trust in distributed environments. Research Design & Methods: This study uses a qualitative approach through the Systematic Literature Review (SLR) method on 25 scientific articles obtained from Scopus (18 articles), Google Scholar (7 articles), and additional sources through SciSpace. The analysis process was carried out through identification, screening, and thematic content analysis to map the concepts, challenges, and implementation strategies of Zero-Trust in cloud–edge.Findings: The results of the study show that Zero-Trust is understood as an identity-based security framework that emphasizes continuous verification, least privilege, and micro-segmentation. Key challenges include edge device heterogeneity, resource constraints, cross-platform policy orchestration, organizational readiness, and the inconsistency of distributed identity standards. Several effective strategies were identified, including adaptive authentication, identity-first architecture, AI-driven anomaly detection, blockchain integration, and policy-as-code for managing cloud–edge policies. Implications & Recommendations: Implementing Zero-Trust in a cloud-edge environment requires a phased approach that prioritizes identity management, automated policy orchestration, and security control integration tailored to the limitations of edge devices. Organizations are advised to strengthen their technical competencies, improve system interoperability, and adopt a telemetry-based security model. Contribution & Value Added: This research contributes to the latest conceptual synthesis regarding the implementation of Zero-Trust in cloud-edge architecture and fills the research gap related to the challenges and strategies of its application. The analytical framework can be used by practitioners, researchers, and policymakers in designing adaptive and sustainable Zero-Trust architectures.